DNA binding, cleavage, apoptosis and cytotoxicity studies of three heteroleptic nickel complexes bearing beta-diketones - Sousa, Luana M.; Souza, Wesley A.; Paixao, Drielly A.; Fazzi, Rodrigo B.; Tezuka, Daiane Y.; Lopes, Carla D.; Carneiro, Zumira A.; Moreira, Mariete B. [UNESP]; Pivatto, Marcos; Netto, Adelino V. G. [UNESP]; Albuquerque, Sergio de; Ferreira, Francis B.; et al. (Elsevier B.V., 2020)
In this work, three nickel(II) complexes, namely, [Ni(eta(2)-NO3)(bta)(phen)] (I), [Ni(eta(2)-NO3)(btc)(phen)] (II), and [Ni(eta(2)-NO3)(btf)(phen)] (III) (bta = 4,4,4-trifluoro-1-phenyl-1,3-butanedione anion, btc = 1-(4-chlorophenyl)-4,4,4-trifluoro-1,3-butanedione anion, btf = 4,4,4-trifluoro-1-(2-furyl)-1,3-butanedione anion, phen = 1,10-phenanthroline) were prepared and fully characterized by magnetic susceptibility measurements, spectroscopic methods and single-crystal X-ray diffraction. The spectral and structural data confirm that the A-diketones anions coordinate via the oxygen atoms, whilst the heterocyclic base coordinates through the nitrogen atoms. A nitrate coordinated in bidentate mode completes the coordination sphere around the metal center. The anticancer activity of chelating ligands and their nickel complexes was evaluated against two tumor cell lines, MCF-7 (a hormone responsive cancer cell) and MDA-MB-231 (triple negative breast cancer cell). The complexes I and II were more active than cisplatin and interacted more effectively with DNA, with K-b values in the range of 10(3) -10(4) M-1. According to data from circular dichroism (CD) and fluorescence spectroscopy, these complexes appear to bind to the DNA groove and/or by electrostatic forces. Molecular docking followed by semiempirical simulations reinforce that they are capable of binding in the minor groove of the double helix of ct-DNA in an A-T rich region. DNA cleavage studies indicated that the complex II cleaves the plasmid DNA in the presence of H2O2. Subsequently, we found that I and II induce late apoptosis in MCF-7 cells.
Keywords: Nickel complexes; beta-diketones; DNA binding; DNA cleavage; Apoptosis; Cancer